My biggest research mistake : adventures and misadventures in psychological research - Sternberg, Robert J. (Los Angeles, CA : SAGE Publications, Inc., 2020)
KEY FEATURES: A student-friendly writing style makes the content more approachable for readers to retain. Personal stories from fellows of the Association of Psychological Science (APS) convey to readers that even the most distinguished experts make mistakes that can be avoided through examination. Critical thinking questions give students the opportunity to reflect on preceding essays. Stories from all areas of psychology appeal to learners beyond subfields of psychology.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Psychology -- Research